Asymmetric Michael Addition of Cyclohexanone or Cyclopentanone to Chalcones Catalyzed by an L‐Proline‐Based Organic Phosphane. Issue 13 (13th March 2013) - Liu, Lingyan; Zhu, Yunna; Huang, Kaimeng; Chang, Weixing; Li, Jing
Abstract: An organophosphane catalyst derived fromL ‐proline was shown to be a very effective catalyst for asymmetric Michael addition reactions of various chalcones to cyclic ketones including both cyclohexanone and cyclopentanone. The corresponding adducts could be obtained in high yields (up to 91 %) and with excellent enantioselectivities (up to 99 % ee ) and diastereomeric ratios (up to >99:1). A possible catalytic mechanism, based on 31 P NMR and ESI‐MS observations, for this organophosphane‐catalyzed Michael addition has been proposed. Abstract : A simple organophosphane catalyst derived fromL ‐proline was shown to be a very effective catalyst for the asymmetric Michael addition of chalcones to cyclohexanone and to the weakly reactive cyclopentanone. The corresponding adducts could be obtained in high yields (up to 91 %) and with excellent enantioselectivities (up to 99 % ee ) and diastereomeric ratios (up to >99:1).